Teacher Professionalism in Developing Environment-Based Innovative Learning Media through Herbarium - Nur Laili; Jaenullah, Jaenullah (Berkala Ilmiah Pendidikan, 2025)
Learning of Al-Qur'an Hadith in Madrasah Ibtidaiyah still tends to be textual, so students' understanding of the meaning of the verses is often less contextual and meaningful. This study aims to describe teacher professionalism in developing innovative, environment-based learning media through the use of a herbarium. The research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing. The results show that teacher professionalism is reflected in two main activities: planning and environmental exploration based on Qur'anic verses, as well as the preparation and presentation of herbaria as contextual learning media. The use of herbarium media was able to improve students' cognitive understanding, foster affective attitudes such as gratitude and environmental awareness, and develop psychomotor skills through the activities of compiling and presenting their work. This media has advantages because it is contextual, economical, and increases students' active involvement. However, it requires a relatively longer time and depends on the environmental conditions around the madrasah. It is recommended that teachers at MINU continue to develop environment-based learning media and combine them with other innovations to enrich meaningful Al-Qur'an Hadith learning that is oriented toward character building.